(untitled) (Physical Education, Health and Social Sciences, 2025)
Background: Household activities which are performed in awkward posture and continuously without any break can result in musculoskeletal symptoms that result in limitation of the efficiency of the work which is performed. As full time homemakers performed their household activities without any rest break and sometimes in awkward posture that puts stress on their joints and muscles that result in might be chances of musculoskeletal disorders. So, we aimed to evaluate the relationship of musculoskeletal disorders and household activities. Objective: The study aims to evaluate the association of musculoskeletal disorders among housewives because of daily household activities (cooking, washing, dusting, cleaning, and childcare). Methodology: Three hundred sixty-seven participants (housewives) having age of 20-60 across Lahore city were participated in this research study. The study was carried through the Nordic questionnaire and questions about posture. Results: Among 368 participants, majority of the housewives were working for 4-6 hours per day (61.7%), 23.6% were working for 7-9 hours per day and 14.1% were working for 1-3 hours and most of the females adapted both standing and sitting posture during daily household activities and during household activities the major areas that is involved in musculoskeletal symptoms are back (38.3%), knees (26.4%), shoulders (22.3%), neck (16.8%), wrist/hands (9.2%) and ankles/foot (7.6%). Conclusion: The study concluded that there is no association between Pain score and hours of working per day and there is significant association between Pain score and posture during working.